2023
DOI: 10.3847/1538-4357/acd1ed
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Ambient Solar Wind Medium on a CME-driven Shock and the Associated Gradual Solar Energetic Particle Event

Abstract: We present simulation results of a gradual solar energetic particle (SEP) event detected on 2021 October 9 by multiple spacecraft, including BepiColombo (Bepi) and near-Earth spacecraft such as the Advanced Composition Explorer (ACE). A peculiarity of this event is that the presence of a high-speed stream (HSS) affected the low-energy ion component (≲5 MeV) of the gradual SEP event at both Bepi and ACE, despite the HSS having only a modest solar wind speed increase. Using the EUHFORIA (European Heliospheric FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…At Bepi and Earth, all three SEPMOD simulation runs produce fluxes that are higher than observed. While at Bepi this could be due to the packed configuration of the instrument during its cruise phase, implying that the spacecraft itself may screen some particles (see also Appendix A in Palmerio et al, 2022), it is clear that at Earth this is owing to either a too-large SEP injection patch or the specific heliospheric context and Wijsen et al (2023), in fact, showed that there was a solar wind high-speed stream flowing between the CME source region and Earth's location, which may have resulted in particles being partially occulted and/or delayed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At Bepi and Earth, all three SEPMOD simulation runs produce fluxes that are higher than observed. While at Bepi this could be due to the packed configuration of the instrument during its cruise phase, implying that the spacecraft itself may screen some particles (see also Appendix A in Palmerio et al, 2022), it is clear that at Earth this is owing to either a too-large SEP injection patch or the specific heliospheric context and Wijsen et al (2023), in fact, showed that there was a solar wind high-speed stream flowing between the CME source region and Earth's location, which may have resulted in particles being partially occulted and/or delayed.…”
Section: Discussionmentioning
confidence: 99%
“…Jebaraj et al (2023) examined the acceleration of electrons by both the solar flare temporally associated with the parent solar eruption and by the shock driven by the corresponding CME. Finally, Wijsen et al (2023) simulated the propagation of the CME-driven shock and the ESP event at two of the five observers using the European Heliospheric FORecasting Information Asset (EUHFORIA; Pomoell & Poedts, 2018) and PArticle Radiation Asset Directed at Interplanetary Space Exploration (PARADISE; Wijsen et al, 2019) models.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the release time of particles estimated at STA may be influenced by the in situ magnetic field direction (see Section 4.3 below). The effects of inhomogeneities in the ambient medium leading to different particle properties are not discussed here (e.g., Kouloumvakos et al 2022Kouloumvakos et al , 2023Wijsen et al 2023).…”
Section: Particle Acceleration With the Evolution Of The Shockmentioning
confidence: 99%
“…The modeling chain EUHFORIA-PARADISE has been used previously to successfully study and reproduce in situ observed gradual SEP events (e.g., Wijsen et al 2022Wijsen et al , 2023bNiemela et al 2023). In this work, we take a different approach and study a synthetic solar eruptive event that consists of two fast, interacting CMEs.…”
Section: Modelsmentioning
confidence: 99%